High Intensity Interval Training: Cardiorespiratory adaptations, metabolic and performance - Germano, M. D.; Gonsalves Sindorf, M. A.; da Silva, C. A.; Evangelista, A. L.; Bocalini, D. S.; Lopes, C. R. (International Journal of Sports Science, 2015)
High Intensity Interval Training (IT) involves repeating maximum and/or supramaximal sprints for short and/or long periods (= 90 - 120% of the maximum oxygen consumption speed [vVO2max]; = the Maximal Lactate Steady State [MLSS]) separated by recovery periods, which may be passive or by performing exercises in moderate intensity (passive and active pausing, respectively). However, such cardiorespiratory, metabolic, morphological, and performance adaptations depend on manipulating acute variables which guide the continuous training process, including volume, intensity, different times and types of recovery between series, and weekly training schedule. With this in mind, the study aimed to review and discuss various results investigating the effects of TI in cardiorespiratory, metabolic, and performance parameters in athletes and physically active individuals. The most relevant original scientific studies as of September, 2015, were analyzed, using the following databases: Science Citation, Index, Scopus, Sport Discus, The Scielo, and National Library of Medicine, combining the following keywords: endurance training, running training, recovery, repeated sprint, high intensity, speed endurance, interval training, anaerobic, and rest interval. It has been concluded literature has not clearly demonstrated the best combination of training variables, which allow for better efficiency in increasing cardiorespiratory, metabolic, and performance parameters. Most studies have showing effort intensity, when close to maximum cardiorespiratory capacity, results in increased stress and, therefore, greater cardiorespiratory and metabolic adaptations.